2009
DOI: 10.1002/cncr.24697
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator (CFTR) gene mutations and risk for pancreatic adenocarcinoma

Abstract: BACKGROUND: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene are common in white persons and are associated with pancreatic disease. The purpose of this case-control study was to determine whether CFTR mutations confer a higher risk of pancreatic cancer. METHODS: In a case-control study, the authors compared the rates of 39 common cystic fibrosis-associated CFTR mutations between 949 white patients with pancreatic adenocarcinoma and 13,340 white controls from a clinical laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 38 publications
2
63
0
2
Order By: Relevance
“…Even though the overall cancer risk in CF patients is similar to that of the general population, CF patients are at elevated risk (6.5 fold) of developing gastrointestinal cancers including pancreatic cancer [32] . The results from the cohort studies indicate an increased risk for pancreatic cancer among CF patients, which is supported by two recent reports [33,34] , in which multiple CFTR mutations were analyzed. These studies also found that patients who are CFTR mutant carriers develop pancreatic cancer earlier than those who carry normal CFTR.…”
Section: Cftr and Gastrointestinal Cancersupporting
confidence: 71%
See 1 more Smart Citation
“…Even though the overall cancer risk in CF patients is similar to that of the general population, CF patients are at elevated risk (6.5 fold) of developing gastrointestinal cancers including pancreatic cancer [32] . The results from the cohort studies indicate an increased risk for pancreatic cancer among CF patients, which is supported by two recent reports [33,34] , in which multiple CFTR mutations were analyzed. These studies also found that patients who are CFTR mutant carriers develop pancreatic cancer earlier than those who carry normal CFTR.…”
Section: Cftr and Gastrointestinal Cancersupporting
confidence: 71%
“…These studies also found that patients who are CFTR mutant carriers develop pancreatic cancer earlier than those who carry normal CFTR. While there are reports that do not support the view that CFTR mutations increase the risk of pancreatic cancer [35,36] , Maisonneuve et al [23] concluded that there is a consistent increased risk of pancreatic cancer in CF patients, which is supported by retrospective studies that recruited a large amount of cases and screened multiple CFTR mutations [33,34] . The difference between the reported associations of pancreatic risk and CFTR variation could be due to multiple reasons such as limited case number, different parameters regarding selection of the control population, mutations investigated in the study, and environmental factors including smoking and alcohol consumption.…”
Section: Cftr and Gastrointestinal Cancermentioning
confidence: 86%
“…Cystic fibrosis is also correlated with an increased risk of cancer, including thyroid cancer (10). The mutation of the CFTR gene was significantly associated with lung and pancreatic cancer in previous reports (18,19). Although the increased risk of thyroid cancer (OR=9.8, 95% CI=1.2-35.5) may result from either frequent exposure to X-ray or from surveillance bias due to intensive follow up (10), the findings of the present study showed a possible association between genetic factors and thyroid cancer in cystic fibrosis patients.…”
Section: (95% Ci) P-value -------------------------------------------mentioning
confidence: 87%
“…Genetic variations in CFTR may be associated with increased or decreased risk for developing cancers, [44][45][46] suggesting that CFTR is a tumor suppressor or promoter, according to the type of tumor. The high level of CFTR expression is associated with tumor malignancy, progression in ovarian cancer and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%